2014
DOI: 10.1016/j.biortech.2013.10.093
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia removal in food waste anaerobic digestion using a side-stream stripping process

Abstract: Three 35-L anaerobic digesters fed on source segregated food waste were coupled to side-stream ammonia stripping columns and operated semi-continuously over 300 days, with results in terms of performance and stability compared to those of a control digester without stripping. Biogas was used as the stripping medium, and the columns were operated under different conditions of temperature (55, 70, 85 ⁰C), pH (unadjusted and pH 10), and RT (2 to 5 days). To reduce digester TAN concentrations to a useful level a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(33 citation statements)
references
References 19 publications
3
23
0
1
Order By: Relevance
“…This indicated that acetoclastic methanogenesis was able to resume when ammonia inhibition stress was relieved in a timely manner. A similar effect was reported by Serna-Maza et al (2014) who found that the acetoclastic pathway in a mesophilic food waste digester could be recovered when TAN concentration was reduced by ammonia stripping, even after operation over a long period.…”
Section: Methanogenic Pathway Under Ammonia Inhibitionsupporting
confidence: 84%
“…This indicated that acetoclastic methanogenesis was able to resume when ammonia inhibition stress was relieved in a timely manner. A similar effect was reported by Serna-Maza et al (2014) who found that the acetoclastic pathway in a mesophilic food waste digester could be recovered when TAN concentration was reduced by ammonia stripping, even after operation over a long period.…”
Section: Methanogenic Pathway Under Ammonia Inhibitionsupporting
confidence: 84%
“…(Lauterböck et al, 2012;Lin et al, 2013;Rico et al, 2010;Serna-Maza et al, 2014). Indeed, some of the above-mentioned methods exhibited high efficiency of alleviating ammonia inhibition to anaerobic fermentation.…”
Section: Introductionmentioning
confidence: 97%
“…However, common problems that occur during the conventional AD of KWdproblems related to the high oil content and the presence of macromolecular compounds in the wastedinclude the accumulation of lactic acid at an early stage of the digestion process resulting in a dramatic pH drop [38] and inhibitory levels of ammonia, sulphide and long-chain fatty acids [2,23]; these factors usually diminish and impede digestion stability, thus restricting the application of digestion. In order to relieve inhibition caused by these problems, numerous pretreatment methods, such as chemical and thermal pretreatment [3,4,12,22,28], and new process techniques, such as co-digestion with substrates containing high levels of ammonium nitrogen and alkalinity to compensate for their absence in KW [25,43], have been suggested to improve the properties of organic waste to promote biogas production and the solubilisation of particulate organics.…”
Section: Introductionmentioning
confidence: 99%